The TMAO Metabolic Axis in Vascular Disease: A Position Paper on Redox Mechanisms and Priorities for Clinical Translation - Francesca Miceli; Eugenio Caradonna; Claudia Panzano; Wassim Mansour; Fulvio Ferrara; Lucy Costantino; Carlo Setacci; Luca di Marzo (Antioxidants, 2026)
Background: Trimethylamine N-oxide (TMAO) arises from the interaction of diet, gut microbial metabolism, hepatic oxidation, and renal clearance. Experimental work links TMAO exposure to mitochondrial oxidative stress, NLRP3 inflammasome activation, impaired nitric oxide signaling, vascular smooth muscle cell dysfunction, and thrombosis. How far these findings explain human vascular disease remains uncertain. Purpose: We examine TMAO and related metabolites in carotid atherosclerosis, aortic disease (abdominal aortic aneurysm, AAA, and dissection), and peripheral artery disease (PAD), focusing on redox biology and the obstacles that still limit clinical translation. Position: Current evidence makes the pathway biologically credible, but it does not support routine TMAO measurement, a universal cutoff, or treatment decisions based on a single metabolite. The recent association between γ-butyrobetaine and limb outcomes also suggests that TMAO may not always be the most informative component of the pathway. Most causal evidence remains preclinical, and no TMAO-lowering or redox-directed intervention has improved a vascular clinical endpoint. Conclusions: For now, the TMAO pathway remains investigational. Progress will depend on multicenter studies that measure several pathway metabolites with harmonized assays and carefully account for renal function, diet, and sex. Interventional studies are premature until safety and biological target engagement have been established.